Syndecan-1 expression during postnatal tooth and oral mucosa development in rats aged from two days to six weeks - De Angelis Daniel D.; Sampson Wayne J.; Wiebkin Ole W.; Wilson David F. (Sciendo, 2002)
Syndecans are a family of heparan sulphate proteoglycans that regulate cell-matrix interactions that influence cell growth, proliferation and morphology. The aim of this study was to observe changes in the expression of Syndecan-1 in the developing epithelium of the rat oral mucosa and in the epithelial cell rests of Malassez in the developing periodontium of normal rat molars, from late crown development through to early eruption. Immuno-histo-chemistry (Syndecan-1 N-18) and histochemistry (Alcec Blue) were used to observe changes in the expression of Syndecan-1 in rats aged two to 42 days. Results indicated that during normal tooth development in the rat, labelling or staining of variable intensity for Syndecan-1 was demonstrated in the stratified oral epithelium above the stratum basale in the rat tongue and palate, and in ameloblasts of the developing molar in rats aged two to 14 days. Histochemical staining of the predentine and dentine layers was consistent in all specimens. Labelling or staining for Syndecan-1 was negative in the rat periodontal ligament, which may suggest that either Syndecan-1 was not expressed during normal molar root development or that continued work is required for identification of a suitable label in rats.